If you had less than a year to live, would you want to know? A seven‐country European population survey of public preferences for disclosure of poor prognosis. Issue 10 (18th March 2013) - Harding, R.; Simms, V.; Calanzani, N.; Higginson, I. J.; Hall, S.; Gysels, M.; Meñaca, A.; Bausewein, C.; Deliens, L.; Ferreira, P.; Toscani, F.; Daveson, B. A.; et al.
Abstract Objective With increasing European cancer deaths, clinicians must manage information regarding poor prognosis. This study aimed to determine European citizens' preferences, within a scenario of serious illness such as cancer with less than a year to live, for information disclosure regarding poor prognosis, the likely symptoms and problems, and the care options available, to measure variations between countries and to identify factors associated with preferences. Methods A population‐based cross‐national telephone survey using random digit dialling in seven countries was conducted. Results Among 9344 respondents, data revealed an international preference (73.9%) to always be informed in the scenario of having a serious illness such as cancer with less than a year to live. This varied from 67.6% in Italy to 80.7% in Flanders. A minority (21.1%) did not want such information unless they ask, or at all. People younger than 70 years (OR 0.72, 95% CI 0.62–0.83, p < 0.001), men (OR 1.23, 95% CI 1.10–1.37, p < 0.001), those with experience of illness (OR = 1.20. 95% CI 1.01–1.43, p < 0.05) and with more education (OR = 1.20, 95% CI 1.09–1.32, p < 0.001) were more likely to want to know of limited time left. Conclusions The models confirmed the influence of four factors in more than one country (age, gender, education and most concerning problem) and added 11 country‐specific factors to which national policies and clinical practice should respond. These findings confirm a majority public preference to be informed in a scenario of poor prognosis. Policy clinical practice should facilitate elucidation and delivery of preferences. Evidence for effective communication skills‐building interventions for clinicians is required. Copyright © 2013 John Wiley & Sons, Ltd.